HUBUNGAN ANTARA TINGKAT PENDIDIKAN ORANG TUA DENGAN DISIPLIN BELAJAR SISWA KELAS V SD GUGUS I KECAMATAN TANETE RIATTANG KABUPATEN - Amaliah Dwi Cahyani; Muhammad Amran; Mujahidah Mujahidah; Satriani DH Satriani DH (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2021)
This study is a quantitative study using a correlational design which aims to determine the relationship between education level and learning discipline for fifth grade elementary school students in cluster I, Tanete Riattang District, Bone Regency. The population in this study were the fifth grade students of SD Cluster I, Tanete Riattang District, Bone Regency, which amounted to 326 students while the number of samples was 81 using simple random sampling technique. Data collection was carried out in this study by providing a questionnaire. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. Based on descriptive statistical analysis, it is obtained that the mode of education level is SMA level. The learning discipline has an average of 93.87 and a percentage of 93.8% which is in the very good category. The results of the inferential statistical analysis showed tcount ttable at a significance level of 5%. Thus H0 rejected and H1 accepted. From the results of the study, it was concluded that there was a significant relationship between the education level of parents and the learning discipline of fifth graders of SD Cluster I, Tanete Riattang District, Bone Regency.